Pharmacy Educationists on Post-COVID-19: A Lockdown Exit Preparedness Survey - Pattnaik, Satyanarayan; Talla, Varun; Jahan, Qaiser; Swain, Kalpana; Rao, JV (Indian Journal of Pharmaceutical Education and Research, 2021)
Purpose: Most of the educational institutions are now closed in many parts of the world due to the pandemic outbreak of COVID-19. Rebooting the institutions, at the times when an effective therapy or vaccine is still awaited, is very risky. The aim of the study was to assess the post-COVID-19 lockdown exit preparedness of Indian pharmacy educationists. Basic procedures: Pharmacy academicians were included in the study to assess their preparedness for the post-COVID-19 lockdown exit using a cross-sectional survey. Main Findings: A total of 715 pharmacy educationists (37.9% females) participated in the study encompassing all levels of academic positions and teaching experiences from across the country. A majority of the study respondents recommended for frequent sanitization of campus (87.4%), adoption of hand sanitization practice by all (97.1%), face mask usage(96.1%), thermal screening in the campus (92.7 %), reduction in physical class strength (67.6%), social distancing in campus(95.4%), reduction in contact hours (80.1%) and precaution while animal experimentation (88.4%). Principal conclusion: The study revealed the perceptions and recommendations of the study participants for a reboot of the educational institutions in the pandemic situation which may be used by policymakers while devising guidelines for operations of educational institutions during the pandemic situation.
Keywords: SARS-CoV-2; COVID-19; Pandemic preparedness; Educational institution; Social distancing; Education